INSIDER TRADING AND CORPORATE SPINOFFS - Charlie Charoenwong; David K. Ding; Jing Pan (The International Journal of Banking and Finance, 2023)
The study reported here examines insider trading and the issue of undervaluation as a motive behind corporate spinoffs. The results show an unmistakable increase (decrease) in the number of insider purchases (sales) and net purchases (sales) in the four quarters prior to a spinoff announcement. In addition, relative to a benchmark period, insider selling is significantly lower, and their net purchases significantly higher, in the three quarters prior to a spinoff announcement, as compared to other periods. Furthermore, announcement period excess returns for abnormal net insider purchases are significantly higher than excess returns for abnormal net insider sales. However, only firms with abnormal net insider purchases exhibit significant improvement in their long-run market and operating performance after a spinoff. The results seem to suggest that undervaluation is an important motive behind corporate spinoffs and that it is possible to identify the quality of a spinoff firm based on insider trading behavior prior to its announcement.